Composite board as well as preparation method and application thereof
By controlling the amount of PVC resin in the composite sheet and adopting a specific formula SPC layer and honeycomb aluminum layer, the problem of insufficient holding screw force in the composite sheet is solved, and the grasping force is improved and waterproof and moisture-proof performance is achieved.
Patent Information
- Application Number
- CN202411538168.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-10-31
AI Technical Summary
Existing composite panels are prone to falling off the door panel during packaging testing, mainly because of the weak holding screw force.
By controlling the amount of PVC resin in the first SPC layer and the second SPC layer in the laminated structure in the composite sheet material to a suitable double balance of toughness and rigidity, thereby improving the holding screw force. At the same time, a specific formula of SPC layer and honeycomb aluminum layer are used to ensure that the sheet has good waterproof and moisture resistance.
The screw grip force of composite sheets is improved, avoiding the problem of door panel falling off, while maintaining good waterproof and moisture-proof performance, extending the service life of the product.
Smart Images

Figure CN119427869A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of board materials, and in particular to a composite board material and a preparation method and application thereof. Background Art
[0002] With the improvement of people's living standards, bathroom cabinets are more and more widely used, especially bathroom cabinets made of triamine board. However, bathroom cabinets are often in a humid environment during use, and triamine board is prone to water absorption and swelling. In severe cases, the edge banding will fall off, resulting in unusability, seriously affecting the user experience and shortening the product life. Metal bathroom cabinets are gradually entering the public's field of vision. At present, there is a composite board on the market, which is made of SPC board and honeycomb aluminum. It has the advantages of waterproof and moisture-proof, high strength, and can solve the problem of easy dents on the board surface. However, the bathroom cabinet made of this material will have the problem of door panels falling off during the packaging test, mainly because the screw grip is weak. Summary of the invention
[0003] Based on the defects of the prior art, the purpose of this application is to provide a composite plate and a preparation method and application to improve the problem of weak screw holding force of the composite plate formed by SPC plate and honeycomb aluminum.
[0004] In order to achieve the above object, in a first aspect, the present application provides a composite plate, comprising a first SPC layer, a honeycomb aluminum layer and a second SPC layer stacked in sequence, wherein the first SPC layer and the second SPC layer each independently contain the following components in parts by weight:
[0005]
[0006] The inventor discovered during the research process that the screw holding force of the board is closely related to its toughness and rigidity, but the screw holding force is not simply positively correlated or negatively correlated with toughness and rigidity. Only when the toughness and rigidity of the board reach an appropriate double balance, the board has a better screw holding force. The present application controls the amount of PVC resin in the first SPC layer and the second SPC layer within the above-mentioned specific range, so that the toughness and rigidity of the composite board reach an appropriate double balance and have a better screw holding force. At the same time, the first SPC layer and the second SPC layer adopt the above-mentioned specific formula and have good waterproof and moisture-proof properties; the honeycomb aluminum layer itself has good waterproof and moisture-proof properties. Therefore, the composite board of the present application also has good waterproof and moisture-proof properties, which can completely solve the problems caused by water absorption and expansion, and extend the service life of the product.
[0007] In the first SPC layer and the second SPC layer, the PVC resin content is independently 20-40 parts by weight, such as 20 parts by weight, 22 parts by weight, 24 parts by weight, 26 parts by weight, 28 parts by weight, 30 parts by weight, 32 parts by weight, 34 parts by weight, 36 parts by weight, 38 parts by weight, 40 parts by weight or an interval formed by any two of the above values. Preferably, in the first SPC layer and the second SPC layer, the PVC resin content is independently 25-35 parts by weight, so that the composite board has a stronger screw holding force.
[0008] Preferably, the content of the PVC resin in the first SPC layer and the content of the PVC resin in the second SPC layer are each independently greater than 19.6%. For example, the two contents are each independently 19.6%, 20%, 22%, 24%, 26%, 28%, 30%, 32%, 34%, 36%, 38%, 39% or an interval formed by any two of the above values.
[0009] Preferably, the honeycomb holes of the honeycomb aluminum layer are hexagonal in shape, and the side length of the honeycomb holes is less than 4 mm. For example, the side length of the honeycomb holes is 4 mm, 3.8 mm, 3.6 mm, 3.4 mm, 3.2 mm, 3 mm, 2.5 mm, 2 mm, or an interval formed by any two of the above values.
[0010] When the side length of the honeycomb hole is less than 4 mm, not only the bonding strength between the honeycomb aluminum layer and the first SPC layer and the second SPC layer is higher, the screw holding force of the composite plate is stronger, and the strength of the honeycomb aluminum layer is higher.
[0011] Preferably, the honeycomb hole side length is 3-4 mm. At present, the honeycomb hole side length of honeycomb aluminum circulated on the market is mainly above 3 mm. Controlling the honeycomb hole side length within the range of 3-4 mm makes honeycomb aluminum material easy to obtain.
[0012] Preferably, the first adhesive layer and the second adhesive layer contain polyurethane glue, and the content of the polyurethane glue in the first adhesive layer and the second adhesive layer is independently 74.5-120 g / m 2 .
[0013] By controlling the content of the polyurethane adhesive in the first adhesive layer and the second adhesive layer within the above-mentioned specific range, the bonding strength between the honeycomb aluminum layer and the first SPC layer and the second SPC layer is higher, and the screw holding force of the plate is also stronger.
[0014] Preferably, the calcium zinc soap stabilizer in the first SPC layer and the second SPC layer each independently comprises at least one of stearic acid soap, lauric acid soap and oleic acid soap.
[0015] Preferably, the plasticizers in the first SPC layer and the second SPC layer each independently include at least one of dioctyl terephthalate, dioctyl adipate, dioctyl sebacate and methyl chlorostearate.
[0016] Preferably, the heat stabilizers in the first SPC layer and the second SPC layer each independently include at least one of tribasic lead sulfate, dibasic lead phosphite, dibasic lead stearate, basic lead carbonate, zinc stearate, calcium stearate and magnesium stearate.
[0017] Preferably, the lubricants in the first SPC layer and the second SPC layer each independently include at least one of solid paraffin and microcrystalline paraffin.
[0018] Preferably, the PVC resin in the first SPC layer and the second SPC layer includes a PVC small tube material, and the content of the PVC small tube material in the first SPC layer and the second SPC layer is independently 5-10 parts by weight. For example, the content of the PVC small tube material in the first SPC layer is 5 parts by weight, 6 parts by weight, 7 parts by weight, 8 parts by weight, 9 parts by weight, 10 parts by weight or an interval formed by any two of the above values; the content of the PVC small tube material in the second SPC layer is 5 parts by weight, 6 parts by weight, 7 parts by weight, 8 parts by weight, 9 parts by weight, 10 parts by weight or an interval formed by any two of the above values.
[0019] The cost of the PVC small tube material is relatively low. By using the PVC small tube material to provide part of the PVC resin and controlling the amount of the PVC small tube material within the above-mentioned specific range, the composite board can have better screw holding force while having lower costs.
[0020] Without impairing the technical effect of the present application, the first SPC layer and the second SPC layer also contain large tube materials.
[0021] Preferably, the thickness of the first SPC layer and the second SPC layer are independently 1.5-2.5mm. For example, the thickness of the first SPC layer is 1.5mm, 1.7mm, 1.9mm, 2mm, 2.2mm, 2.4mm, 2.5mm or an interval formed by any two of the above values; the thickness of the second SPC layer is 1.5mm, 1.6mm, 1.7mm, 1.8mm, 1.9mm, 2mm, 2.1mm, 2.2mm, 2.3mm, 2.4mm, 2.5mm or an interval formed by any two of the above values. The thickness of the first SPC layer and the thickness of the second SPC layer are controlled within the range of 1.5-2.5mm to make the composite sheet stronger and the screw holding force stronger at a lower cost.
[0022] Preferably, the thickness of the honeycomb aluminum layer is 8-20 mm. For example, the thickness of the honeycomb aluminum layer is 8 mm, 10 mm, 12 mm, 14 mm, 16 mm, 18 mm, 20 mm or an interval formed by any two of the above values. Honeycomb aluminum has high strength, high specific stiffness and light weight. Controlling the thickness of the honeycomb aluminum layer within the range of 8-20 mm helps to improve the mechanical properties of the product.
[0023] Preferably, the thickness of the composite sheet is 12-25 mm. For example, the thickness of the composite sheet is 12 mm, 13 mm, 14 mm, 15 mm, 16 mm, 17 mm, 18 mm, 19 mm, 20 mm, 21 mm, 22 mm, 23 mm, 24 mm, 25 mm or an interval formed by any two of the above values.
[0024] Preferably, the composite board further comprises a first facing layer, a second facing layer, a third adhesive layer and a fourth adhesive layer, wherein:
[0025] The first finishing layer is bonded to the surface of the first SPC layer away from the honeycomb aluminum layer through the third adhesive layer;
[0026] The second finishing layer is bonded to the surface of the second SPC layer facing away from the honeycomb aluminum layer through the fourth adhesive layer.
[0027] Preferably, the thickness of the first finishing layer and the second finishing layer are independently 0.15-0.25 mm. For example, the thickness of the first finishing layer is 0.15 mm, 0.16 mm, 0.17 mm, 0.18 mm, 0.19 mm, 0.20 mm, 0.21 mm, 0.22 mm, 0.23 mm, 0.24 mm, 0.25 mm or an interval formed by any two of the above values; the thickness of the second finishing layer is 0.15 mm, 0.16 mm, 0.17 mm, 0.18 mm, 0.19 mm, 0.20 mm, 0.21 mm, 0.22 mm, 0.23 mm, 0.24 mm, 0.25 mm or an interval formed by any two of the above values.
[0028] Preferably, the third adhesive layer and the fourth adhesive layer contain polyurethane glue, and the content of the polyurethane glue in the third adhesive layer and the fourth adhesive layer is independently 74.5-120 g / m 2 .
[0029] Preferably, the first finishing layer and the second finishing layer are each independently a PVC film layer or a PET film layer.
[0030] More preferably, the first facing layer and the second facing layer are each independently a PVC film layer. PVC film is a more common facing material in composite panels, with a wide range of sources, easy to obtain, and low price.
[0031] The content of the polyurethane adhesive in the third adhesive layer and the fourth adhesive layer is controlled within the above-mentioned specific range, so that the bonding strength between the first SPC layer and the first finishing layer, and between the second SPC layer and the second finishing layer is higher, thereby preventing the first finishing layer and the second finishing layer from falling off.
[0032] In a second aspect, the present application provides a method for preparing the composite board, comprising the following steps:
[0033] According to the formula of the first SPC layer and the second SPC layer, calcium carbonate, kaolin, PVC resin, chlorinated polyethylene, calcium zinc soap stabilizer, plasticizer, heat stabilizer and lubricant are mixed, dispersed and extruded to obtain a first SPC board and a second SPC board;
[0034] The first SPC board, the honeycomb aluminum and the second SPC board are bonded in sequence using a first adhesive, and then a first pressing is performed. Then, a PVC film is bonded to the surfaces of the first SPC board and the second SPC board facing away from the honeycomb aluminum using a second adhesive, and then a second pressing is performed to obtain a composite board.
[0035] Preferably, during the preparation of the first SPC board and the second SPC board, the molding temperature is independently 150-180° C.;
[0036] Preferably, the first adhesive comprises polyurethane adhesive, and the coating amount of the first adhesive is 74.5-120 g / m 2 The honeycomb aluminum and the first SPC plate and the second SPC plate are bonded with polyurethane glue, and the amount thereof is controlled within the above-mentioned specific range, thereby improving the bonding strength therebetween and also improving the screw holding force of the plate.
[0037] Preferably, the first pressing pressure is 30-50 tons, the pressing temperature is 150-180° C., and the holding time is 7-15 hours.
[0038] Preferably, the second adhesive comprises polyurethane adhesive, and the coating amount of the second adhesive is 74.5-120 g / m 2 .
[0039] Preferably, the second pressing pressure is 30-50 tons, the pressing temperature is 150-180° C., and the holding time is 7-15 hours.
[0040] Preferably, the production line speed of the composite board is 18-25 m / min.
[0041] In a third aspect, the present application provides an application of the composite board in a bathroom cabinet. The composite board can be used as a main cabinet bottom plate, side plate, pull bar, viewing plate, door plate and other plates of the bathroom cabinet.
[0042] The bathroom cabinet comprises a main cabinet bottom plate, side plates, pull strips, a viewing plate and a door plate, and the material of at least one of the main cabinet bottom plate, side plates, pull strips, the viewing plate and the door plate comprises the composite board material.
[0043] Compared with the prior art, the beneficial effects of the present application are as follows: the present application controls the amount of PVC resin in the first SPC layer and the second SPC layer within a specific range, so that the toughness and rigidity of the composite board achieve a suitable double balance and have better screw holding force; at the same time, the first SPC layer and the second SPC layer are made of a specific formula and have good waterproof and moisture-proof properties; the honeycomb aluminum layer itself has good waterproof and moisture-proof properties, therefore, the composite board of the present application also has good waterproof and moisture-proof properties, can completely solve the problems caused by water absorption and expansion, and extend the service life of the product. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 It is a schematic diagram of the structure of the composite board obtained in Example 1, wherein 1 is a honeycomb aluminum layer, 21 is a first SPC layer, 22 is a second SPC layer, 31 is a first finishing layer, and 32 is a second finishing layer. DETAILED DESCRIPTION
[0045] In order to better illustrate the purpose, technical scheme and advantages of the present application, the present application will be further described below in conjunction with specific embodiments and comparative examples, the purpose of which is to understand the content of the present application in detail, rather than to limit the present application. All other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present application. The experimental reagents and instruments involved in the implementation of this application are all commonly used ordinary reagents and instruments unless otherwise specified. In the present application, the technical features described in an open manner include closed technical schemes composed of the listed features, and also include open technical schemes containing the listed features.
[0046] Example 1
[0047] This embodiment provides a composite board, comprising a first facing layer 31, a third adhesive layer (not shown) stacked in sequence. Figure 1 ), the first SPC layer 21, the first adhesive layer (not shown in Figure 1 ), honeycomb aluminum layer 1, second adhesive layer (not shown in Figure 1 ), the second SPC layer 22, the fourth adhesive layer (not shown in Figure 1 ) and a second finishing layer 32, wherein,
[0048] The shape of the honeycomb holes of the honeycomb aluminum layer 1 is hexagonal, the side length of the honeycomb holes is 3 mm, and the thickness of the layer is 14 mm;
[0049] The first adhesive layer and the second adhesive layer are polyurethane adhesive, and the coating amount of both is 100g / m 2 ;
[0050] The compositions of the first SPC layer 21 and the second SPC layer 22 are shown in Table 1, wherein the calcium zinc soap stabilizer is stearic acid soap, the plasticizer is dioctyl terephthalate, the heat stabilizer is tribasic lead sulfate, the lubricant is solid paraffin, and the thickness of the first SPC layer 21 and the second SPC layer 22 are both 2 mm;
[0051] The third and fourth adhesive layers are polyurethane adhesives, and the coating amount of both is 100g / m 2 ;
[0052] The first finishing layer 31 and the second finishing layer 32 are PVC films, both of which have a thickness of 0.20 mm;
[0053] The thickness of the composite plate is 19 mm.
[0054] The preparation method of the composite board of this embodiment comprises the following steps: according to the formula in Table 1, all raw materials are mixed, dispersed, and extruded to obtain an SPC board, wherein the molding temperature is 170° C.;
[0055] Polyurethane glue is applied on one side of an SPC board, and honeycomb aluminum is laid on the surface after the glue coating is completed. Then, polyurethane glue (with shark lines) is applied on one side of another SPC board and bonded to the honeycomb aluminum to obtain a three-layer structure of SPC board-honeycomb aluminum-SPC board. The obtained three-layer structure of SPC board-honeycomb aluminum-SPC board is directly placed on a press for pressing. The pressing pressure is 40 tons, the pressing temperature is 165°C, and the holding time is 10 hours. The amount of polyurethane glue applied on the SPC board is 100g / m 2 ;
[0056] The PVC film is bonded to both sides of the laminated SPC board-honeycomb aluminum-SPC board three-layer structure using polyurethane glue (Henkel), and the glue coating amount on each side is 100g / m 2 , and then directly put it on the press for pressing, the pressing pressure is 40 tons, the pressing temperature is 170℃, the holding time is 10h, and the production line speed is 22m / min to obtain a composite sheet.
[0057] Examples 2 to 9 and Comparative Examples 1 to 2
[0058] These embodiments and comparative examples all provide a composite board material. These composite boards differ from those in Example 1 in that the compositions of the first SPC layer 21 and the second SPC layer 22 are different. The specific formulas of the first SPC layer 21 and the second SPC layer 22 are shown in Table 1, wherein the types of calcium zinc soap stabilizer, plasticizer, heat stabilizer and lubricant are the same as those in Example 1. In addition, the preparation methods of these composite boards are the same as those in Example 1.
[0059] Table 1
[0060]
[0061] Embodiments 10 to 11
[0062] These embodiments all provide a composite plate material. These composite plates differ from Embodiment 1 in that the honeycomb holes of the honeycomb aluminum layer 1 have different side lengths.
[0063] In Example 10, the honeycomb hole side length of the honeycomb aluminum layer 1 is 4 mm.
[0064] In Example 11, the honeycomb hole side length of the honeycomb aluminum layer 1 is 5 mm;
[0065] The preparation methods of these composite panels are the same as those in Example 1.
[0066] Embodiments 12 to 15
[0067] These embodiments all provide a composite board. The difference between these composite boards and embodiment 1 is that the coating amounts of the first adhesive layer and the second adhesive layer are different.
[0068] In Example 12, the coating weight of the first adhesive layer and the second adhesive layer is 74.5 g / m 2 , the thickness of the composite sheet is 18.9mm;
[0069] In Example 13, the coating amount of the first adhesive layer and the second adhesive layer is 120 g / m 2 , the thickness of the composite sheet is 19.1mm;
[0070] In Example 14, the coating weight of the first adhesive layer and the second adhesive layer is 65 g / m 2 , the thickness of the composite sheet is 18.78mm;
[0071] In Example 15, the coating weight of the first adhesive layer and the second adhesive layer is 140 g / m 2 , the thickness of the composite sheet is 19.5mm;
[0072] The preparation methods of these composite boards are the same as those of Example 1 except that the amount of polyurethane glue applied is adjusted accordingly.
[0073] Embodiments 16 to 17
[0074] These embodiments all provide a composite sheet material, which is different from Embodiment 1 in that the thicknesses of the honeycomb aluminum layer 1, the first SPC layer 21, the second SPC layer 22, the first finishing layer 31, the second finishing layer 32 and the composite sheet material are different, and the types of calcium zinc soap stabilizer, plasticizer, heat stabilizer and lubricant contained in the first SPC layer 21 and the second SPC layer 22 are different (and the glue used in the third adhesive layer and the fourth adhesive layer is different, if any), as follows:
[0075] In Example 16, the thickness of the honeycomb aluminum layer 1 is 9 mm, the thickness of the first SPC layer 21 and the second SPC layer 22 are both 1.5 mm, the thickness of the first finishing layer 31 and the second finishing layer 32 are both 0.15 mm, the thickness of the obtained composite board is 12.9 mm, the calcium zinc soap stabilizer is lauric acid soap, the plasticizer is dioctyl adipate, the heat stabilizer is dibasic lead phosphite, the lubricant is microcrystalline wax, and the first adhesive layer, the second adhesive layer, the third adhesive layer and the fourth adhesive layer are all made of polyurethane glue (with shark);
[0076] In Example 17, the thickness of the honeycomb aluminum layer 1 is 19 mm, the thickness of the first SPC layer 21 and the second SPC layer 22 are both 2.5 mm, the thickness of the first finishing layer 31 and the second finishing layer 32 are both 0.25 mm, the thickness of the obtained composite plate is 25.1 mm, the calcium zinc soap stabilizer is oleic acid soap, the plasticizer is methyl chlorostearate, the heat stabilizer is zinc stearate, and the lubricant is microcrystalline wax;
[0077] The preparation methods of these composite panels are the same as those in Example 1.
[0078] Test Case
[0079] The composite panels obtained from the above embodiments and comparative examples were tested as follows:
[0080] (1) The screw holding force is measured according to 4.21 of GB / T 17657-2022 Test methods for physical and chemical properties of wood-based panels and veneered wood-based panels. PA embedded nuts and self-tapping screws are mainly used for screw holding force test. The screws are placed in a constant temperature and humidity chamber at a temperature of 20°C and a humidity of 65% until the mass is constant. After the screws are driven in, they are pulled out at a uniform speed of 5 mm / min. The test results show that the greater the force required to pull out the screws, the better the performance of the board.
[0081] (2) Determine the peeling resistance according to 4.20 of GB / T 17657-2022 Test Method for Physical and Chemical Properties of Artificial Boards and Faced Artificial Boards. Place the sample in a constant temperature and humidity chamber at 20°C and 65% until the mass is constant. Cut into the SPC board from 10 mm from one end and pull the SPC board apart by half. The upper and lower clamps of the tensile testing machine clamp the peeling end of the SPC board and the peeled SPC board respectively. Place the sample vertically and pull the sample apart at a constant speed. The larger the peeling force, the better the performance of the board.
[0082] (3) The composite board is made into a bathroom cabinet. The specific preparation method is as follows:
[0083] ① Use a cutting machine to cut the composite board into the required sizes of the main cabinet bottom plate, side plate, tie bar, look plate and door plate;
[0084] ②Edge sealing: Use PVC edge banding strips for edge sealing;
[0085] ③ Punching: Use six-sided drilling to make holes;
[0086] ④Assembly: Use the four-in-one connector to connect the main cabinet bottom plate, side plate, pull bar, look plate and door plate to make a bathroom cabinet. Perform a drop test according to QBT 4465-2013 general technical requirements for furniture packaging; after the test, the product is intact and there is no abnormal sound when shaking, indicating that the performance of the board is good.
[0087] The test results are shown in Table 2.
[0088] Table 2
[0089]
[0090]
[0091] It can be seen from the above data that the composite board material of the embodiment of the present application has good screw holding force, such as the screw holding force is above 450N; the first SPC layer and the second SPC layer have a strong peeling force with the honeycomb aluminum layer, such as the peeling force is above 40N, and the door panel of the bathroom cabinet made thereof is not easy to fall off, and the cabinet door does not make abnormal noise when shaking after the drop test.
[0092] By comparing Examples 1 to 5 with Comparative Examples 1 to 2, it can be seen that when the amount of PVC resin in the first SPC layer and the second SPC is too low, the toughness of the composite board is weak, resulting in weak screw holding force; when the amount of PVC resin in the first SPC layer and the second SPC is too high, the rigidity of the composite board is weak, resulting in weak screw holding force; when the amount of PVC resin in the first SPC layer and the second SPC is 20-40 parts by weight, especially 25-35 parts by weight, the composite board has better screw holding force.
[0093] From the comparison between Examples 1 and 10 to 11, it can be seen that when the side length of the honeycomb holes of the honeycomb aluminum layer is less than 4 mm, the screw holding force is stronger, and the peeling force between the first SPC layer and the second SPC layer and the honeycomb aluminum layer is also stronger.
[0094] Comparison of Examples 1, 12 to 15 shows that when the amount of polyurethane glue applied is 74.5-120 g / m 2 When it is within the range, the screw holding force is stronger, and the peeling force between the first SPC layer and the second SPC layer and the honeycomb aluminum layer is also stronger.
[0095] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present application rather than to limit the scope of protection of the present application. Although the present application has been described in detail with reference to the preferred embodiments, ordinary technicians in this field should understand that the technical solution of the present application can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present application.
Claims
1. A composite sheet, characterized in that: The invention comprises a first SPC layer, a first adhesive layer, a honeycomb aluminum layer, a second adhesive layer and a second SPC layer stacked in sequence, wherein the first SPC layer and the second SPC layer each independently comprise the following components in parts by weight:
2. The composite sheet material according to claim 1, characterized in that: In the first SPC layer and the second SPC layer, the PVC resin content is independently 25-35 parts by weight.
3. The composite sheet material according to claim 1, characterized in that: The honeycomb holes of the honeycomb aluminum layer are hexagonal in shape, and the side length of the honeycomb holes is less than 4 mm; preferably, the side length of the honeycomb holes is 3-4 mm.
4. The composite sheet material according to claim 1, characterized in that: The first adhesive layer and the second adhesive layer contain polyurethane glue, and the content of the polyurethane glue in the first adhesive layer and the second adhesive layer is independently 74.5-120 g / m 2 .
5. The composite sheet material according to claim 1, characterized in that: The first SPC layer and the second SPC layer satisfy at least one of conditions A1 to A10: A1. The calcium zinc soap stabilizer in the first SPC layer and the second SPC layer independently comprises at least one of stearic acid soap, lauric acid soap and oleic acid soap; A2. The plasticizers in the first SPC layer and the second SPC layer each independently include at least one of dioctyl terephthalate, dioctyl adipate, dioctyl sebacate and methyl chlorostearate; A3. The heat stabilizer in the first SPC layer and the second SPC layer independently comprises at least one of tribasic lead sulfate, dibasic lead phosphite, dibasic lead stearate, basic lead carbonate, zinc stearate, calcium stearate and magnesium stearate; A4. The lubricant in the first SPC layer and the second SPC layer independently comprises at least one of solid paraffin and microcrystalline paraffin; A5. The PVC resin in the first SPC layer and the second SPC layer includes a PVC small tube material, and the content of the PVC small tube material in the first SPC layer and the second SPC layer is independently 5-10 parts by weight; A6. The thickness of the first SPC layer and the second SPC layer are each independently 1.5-2.5 mm; A7. The thickness of the honeycomb aluminum layer is 8-20mm; A8. The thickness of the composite board is 12-25 mm.
6. The composite sheet material according to claim 1, characterized in that: The composite board further comprises a first facing layer, a second facing layer, a third adhesive layer and a fourth adhesive layer, wherein: The first finishing layer is bonded to the surface of the first SPC layer away from the honeycomb aluminum layer through the third adhesive layer; The second finishing layer is bonded to the surface of the second SPC layer facing away from the honeycomb aluminum layer through the fourth adhesive layer.
7. The composite sheet material according to claim 6, characterized in that: At least one of the following conditions is also met: B1. The thickness of the first finishing layer and the second finishing layer are each independently 0.15-0.25 mm; B2. The third adhesive layer and the fourth adhesive layer contain polyurethane glue, and the content of the polyurethane glue in the third adhesive layer and the fourth adhesive layer is independently 74.5-120g / m 2 ; B3. The first finishing layer and the second finishing layer are each independently a PVC film layer or a PET film layer.
8. A method for preparing a composite board according to claim 6 or 7, characterized in that: The following steps are involved: According to the formula of the first SPC layer and the second SPC layer, calcium carbonate, kaolin, PVC resin, chlorinated polyethylene, calcium zinc soap stabilizer, plasticizer, heat stabilizer and lubricant are mixed, dispersed, and extruded to obtain a first SPC board and a second SPC board; The first SPC board, the honeycomb aluminum and the second SPC board are bonded in sequence using a first adhesive, and then a first pressing is performed. Then, a PVC film is bonded to the surfaces of the first SPC board and the second SPC board facing away from the honeycomb aluminum using a second adhesive, and then a second pressing is performed to obtain a composite board.
9. The method for preparing a composite plate according to claim 8, characterized in that: At least one of the following conditions is met: C1. During the preparation of the first SPC board and the second SPC board, the molding temperature is independently 150-180°C; C2. The first adhesive includes polyurethane adhesive, and the coating amount of the polyurethane adhesive is 74.5-120g / m 2 ; C3. The first pressing pressure is 30-50 tons, the pressing temperature is 150-180 ° C, and the holding time is 7-15h; C 4. The second adhesive is polyurethane adhesive, and the coating amount of the second adhesive is 74.5-120g / m 2 ; C 5. The second pressing pressure is 30-50 tons, the pressing temperature is 150-180°C, and the holding time is 7-15h.
10. Use of the composite board according to any one of claims 1 to 7 in a bathroom cabinet.
Citation Information
Patent Citations
SPC board and preparation method thereof
CN111944252A
Green and environment-friendly PVC color film and preparation method thereof
CN112280218A
Novel micro-foaming SPC wallboard and processing method and device
CN114055600A
Plate structure of cabinet body
CN201471798U
Aluminum honeycomb stone plastic wallboard structure
CN221481258U